2010
DOI: 10.1126/scisignal.2000769
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin–Biased Agonism of the Angiotensin Receptor Induced by Mechanical Stress

Abstract: Abstractβ-Arrestins, which were originally characterized as terminators of heterotrimeric guanine nucleotidebinding protein (G protein)-coupled receptor (GPCR) signaling, also act as important signal transducers. An emerging concept in GPCR signaling is β-arrestin-biased agonism, in which specific ligand-activated GPCR conformational states selectively signal through β-arrestins, rather than through G proteins. Here, we show that mechanical stretch induced β-arrestin-biased signaling downstream of angiotensin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
191
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(200 citation statements)
references
References 62 publications
7
191
1
1
Order By: Relevance
“…The mutation-induced conformational changes were analyzed by RCAM analysis of four Cys reporters introduced in ECL2. In our previous study RCAM was shown to depict specific conformational changes in ECL2 upon binding of the ligand in the orthosteric site of cell surface AT1R in the intact cells under conditions used for signal transduction studies (27)(28)(29)(30)(31). The RCAM analysis in this study indicated the presence of a distinct ECL2 lid conformation in the empty state of the gain of function AT1R mutant but not in the loss of function receptor mutant.…”
Section: Discussionmentioning
confidence: 54%
“…The mutation-induced conformational changes were analyzed by RCAM analysis of four Cys reporters introduced in ECL2. In our previous study RCAM was shown to depict specific conformational changes in ECL2 upon binding of the ligand in the orthosteric site of cell surface AT1R in the intact cells under conditions used for signal transduction studies (27)(28)(29)(30)(31). The RCAM analysis in this study indicated the presence of a distinct ECL2 lid conformation in the empty state of the gain of function AT1R mutant but not in the loss of function receptor mutant.…”
Section: Discussionmentioning
confidence: 54%
“…In cardiac cells, EGFR transactivation has been linked to angiotensin (Rakesh et al, 2010), muscarinic (Krieg et al, 2002;Krieg et al, 2004;Miao et al, 2015), endothelin (Kodama et al, 2002;Chen et al, 2006), opioid (Cao et al, 2005;Cohen et al, 2007;Forster et al, 2007;Zhang et al, 2015), bradykinin (Methner et al, 2009), adrenergic (Noma et al, 2007;Grisanti et al, 2014), adenosine (Williams-Pritchard et al, 2011), and sphoingosine-1 phosphate (S1P) (Hofmann et al, 2009) GPCRs, with transactivation via angiotensin II (Ang II) perhaps the most well studied. Several Gq-linked receptors (Ang II, ET-1, -ARs) may promote cardiac hypertrophy/remodelling, whereas transactivation by adenosine, opioid, bradykinin or muscarinic receptors may be protective, enhancing cell survival.…”
Section: Mechanisms Of Egfr Transactivationmentioning
confidence: 99%
“…Cardiac protection and survival kinase activation in response to adenosine receptor agonism (and ischaemic preconditioning) is also associated with EGFR phosphorylation and blocked by EGFR, MMP or HB-EGF inhibitors (Williams-Pritchard et al, 2011). Finally, mechanical stress has been shown to trigger β-arrestin-dependent AT1 receptor activation, leading to EGFR transactivation and protection of cardiac myocytes from apoptosis (Rakesh et al, 2010).…”
Section: Role Of the Egfr In Gpcr-triggered Cardioprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it concerns β-arrestins, they can also function as molecular mediators of G protein-independent signaling by activating a variety of transduction proteins like Src family kinases and components of the MAPK cascades [166,168,169] . On the basis of these findings, β-arrestins were included among the signaling factors mediating the action of diverse GPCRs in cancer [170] .…”
Section: β-Arrestins: Novel Transducers Of Gpcr Signalsmentioning
confidence: 99%